PENINGKATAN KUALITAS PELAYANAN UNTUK MENINGKATKAN KEPUASAN KONSUMEN PADA PENJUALAN FASHION X - Fernando, Ferry; Hastuti, Rini Tri; Utama, Louis (Jurnal Serina Abdimas, 2024)
Improving service quality in the fashion industry has become a priority in efforts to increase customer satisfaction. This research seeks to identify key factors that influence service quality and explain their impact on customer satisfaction. The research methods used in this research include customer surveys and data analysis to examine customer perceptions of the quality of service provided by retailers. The research results show that aspects such as acceptance, trust, empathy, product safety and reliability play an important role in determining service quality. Additionally, the research includes implementing staff development, training, and information technology initiatives to improve operational efficiency and respond more quickly to customer needs. By leveraging new technology, businesses can improve customer interactions, provide personalized shopping experiences, and simplify the purchasing process. With the implementation of these changes, it is hoped that there will be a significant increase in customer satisfaction. Improving service quality is expected to increase customer loyalty, open opportunities for repeat business and support long-term business growth. This research provides valuable information for those in the fashion industry to identify areas that need improvement to ensure better service and customer satisfaction. Additionally, this research provides a basis for further research and ongoing efforts to improve the quality of work and conditions in the fashion industry. What services does Fashion X provide to customers and how can the quality of Fashion X services increase customer satisfaction, and what is the system for measuring customer satisfaction regarding the quality of Fashion X services? By using five SERVQUAL indicators, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy, and listening to criticism and suggestions from customers